Selective functionalization of azines via phosphonium salts - Koniarczyk, J. Luke, author; McNally, Andrew, advisor; Chen, Eugene, committee member; Barisas, George, committee member; Chatterjee, Delphi, committee member (Colorado State University. Libraries, 2020)
Pyridines and diazines are ubiquitous in pharmaceuticals, agrochemicals, and materials. Therefore, methods to functionalize these structural motifs are increasingly valuable. We have shown that phosphonium salts can be formed on a range of azines, including complex biologicallyactive compounds. Additionally, these azinyl phosphonium salts serve as a general functional handle to facilitate a variety of bond formations. Chapter 2 focuses on a method to incorporate deuterium and tritium atoms onto azines and pharmaceuticals using azinyl phosphonium salts. Deuteration is commonly used as a means to deter unwanted oxidative metabolism on drugs, and tritium is installed as a radiolabel for metabolic studies in the pharmaceutical industry. The protocol of the reaction is simple, and it functions on a wide range of building blocks and complex molecules. Additionally, the tritiation protocol was effectively applied on a selection of drug molecules through a collaborative effort with Merck. In chapter 3, a pyridine-pyridine coupling reaction is discussed using azinyl phosphonium salts as radical precursors. The reaction functions through a radical-radical coupling mechanism using B2pin2 and 4-cyanopyridine as an electron-transfer reagent for reduction of the phosphonium salt. Azinyl phosphonium salts were found to be the only radical precursor amenable to the reaction, and the process functions as an alternative to the Minisci reaction to form bipyridine products.